Raised cosine/NRZ line coding techniques for upgrading free space optical communication systems through various levels of fog - Aadel M. Alatwi; Ahmed Nabih Zaki Rashed (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
This study examines raised cosine/NRZ line coding techniques for upgrading free space optical (FSO) communication systems through various levels of fog.The max. Q factors are simulated and estimated for clear air, light fog, and moderate fog weather conditions at a data rate of 20 Gb/s. The optical signal to noise ratio is also measured for different weather conditions. The total power after both FSO channel and avalanche photodiode (APD) photo-detector receiver is estimated by an optical power meter for max. distances.The study shows that the max. propagation distance is extended to 50 kmthrough clear air, 2.25 km through light fog, and 1.6 km through moderate fog with acceptable max. Q factor